IN VITRO MICROGRAFTING OF RED GLOBE (VITIS VINIFERA L) - S., Osama. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out to evaluate the micrografting success of Red globe cultivar (Vitis vinifera L.) on three rootstocks Ramsey, Freedom and SO4 and investigate the effect of some factors on the micrografting success. Furthermore, compatibility in the graft union was studied. The results showed that Red globe on un-rooted Freedom achieved the highest percentages of scion survival (100.00 %), scion bud burst (60.00%), graft union formation (60.00%), and rooting (40.00%), also longest shoot (2.00cm), highest root number (8.00) and root length (4.50cm). Murashige and Skoog (MS) medium Supplemented with Indole Butyric Acid (IBA) at 1mgL-1 achieved the highest percentages of scion survival (95.20%), scion bud burst (65.43%), graft union formation (82.22%) also, longest shoots (1.84 cm) and maximum average leaf number (2.50). Regarding the effect of MS strength, 25% MS, 50% MS and 75% MS achieved positive effects on all parameters compared with full MS. The anatomical study revealed that Red globe on Freedom combinations were the best due to enough callus formation, less necrotic layers, and a wavy continuity of new cambium were determined. Sterilized 1:1:1 (v:v) peatmoss+perlite+sand mix gave the highest survival rate (100.00%) and showed superior vegetative growth. Freedom micrografts achieved the highest survival rate (100.00%), better growth and longer roots compared with those on SO4 and Ramsey (80, 70%) respectively.